2017
DOI: 10.1111/ans.14276
|View full text |Cite
|
Sign up to set email alerts
|

Similar length of colon is removed regardless of localization in right‐sided colonic cancer surgery

Abstract: Length of resected colon does not differ depending on localization of tumour in our center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Although there were controversial results concerning the association of the length of resected bowel and the LN yield [1,3,10,11,14,15], some authors also tried to find the cutoff values of specimen lengths for adequate LN counts. They showed that there should be almost < 20 cm of specimen length for sufficient LN counts [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there were controversial results concerning the association of the length of resected bowel and the LN yield [1,3,10,11,14,15], some authors also tried to find the cutoff values of specimen lengths for adequate LN counts. They showed that there should be almost < 20 cm of specimen length for sufficient LN counts [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Although the length of resected colon is dependent on mucosal margins, arterial anatomic variations, and extent of lymphadenec-tomy, resection of longer colonic segments with larger mesocolic mesentery may also lead to higher counts of LN [10]. An increase in the number of retrieved LNs with increasing length of resected colon segments has been shown [3,8,[11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It is beneficial to ensure the precision of anatomical separation, obtain sufficient tumor incisional margin and reduce trauma, which promote body function and recovery time shortening. However, laparoscopic surgery has high requirements for the operator’s skills, and the uterus, small intestine and other adjacent organs during the operation will affect the operation, which prolongs the operation time to a certain extent[ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%